5-ASEAN Countries and China on Education and Economic Growth: A Vector Error Correction Analysis. (July 2022) - Cabauatan, Ronaldo R.
This study estimates the impact of education sector of the 5-ASEAN members and China in the long-run. This study also examines the long-run relationship of the education sector and the economy. This compares the number of enrollees in the 5-ASEAN countries plus China. Having the 2015 ASEAN integration, it is important to determine the contribution of education to the economy. This study determines the causality between the education enrollees and real GDP in 5-ASEAN countries plus China. This study also used the structural stability test to examine the stability of the coefficients of the model between different time periods as this will provide insights concerning the stability or consistency despite the economic environment in previous years. The study made used of the specification error test to determine if there is specification error in the results. The study also used the unit root test in determining the stationarity of the time series data that may result to spurious regression output. The study used White heteroskedasticity test to determine if the variance of the residual is constant, unbiased and no outliers.